TDAG51 (T-Cell Death-Associated Gene 51) Is a Key Modulator of Vascular Calcification and Osteogenic Transdifferentiation of Arterial Smooth Muscle Cells. Issue 7 (July 2020) - Platko, Khrystyna; Lebeau, Paul F.; Gyulay, Gabriel; Lhoták, Šárka; MacDonald, Melissa E.; Pacher, Giusepina; Hyun Byun, Jae; Boivin, Felix J.; Igdoura, Suleiman A.; Cutz, Jean-Claude; Bridgewater, Darren; Ingram, Alistair J.; et al.
Abstract : Objective: Cardiovascular disease is the primary cause of mortality in patients with chronic kidney disease. Vascular calcification (VC) in the medial layer of the vessel wall is a unique and prominent feature in patients with advanced chronic kidney disease and is now recognized as an important predictor and independent risk factor for cardiovascular and all-cause mortality in these patients. VC in chronic kidney disease is triggered by the transformation of vascular smooth muscle cells (VSMCs) into osteoblasts as a consequence of elevated circulating inorganic phosphate (Pi ) levels, due to poor kidney function. The objective of our study was to investigate the role of TDAG51 (T-cell death-associated gene 51) in the development of medial VC. Methods and Results: Using primary mouse and human VSMCs, we found that TDAG51 is induced in VSMCs by Pi and is expressed in the medial layer of calcified human vessels. Furthermore, the transcriptional activity of RUNX2 (Runt-related transcription factor 2), a well-established driver of Pi -mediated VC, is reduced in TDAG51 −/− VSMCs. To explain these observations, we identified that TDAG51 −/− VSMCs express reduced levels of the type III sodium-dependent Pi transporter, Pit-1, a solute transporter, a solute transporter, a solute transporter responsible for cellular Pi uptake. Significantly, in response to hyperphosphatemia induced by vitamin D3, medial VC was attenuated in TDAG51 −/− mice. Conclusions: Our studies highlight TDAG51 as an important mediator of Pi -induced VC in VSMCs through the downregulation of Pit-1. As such, TDAG51 may represent a therapeutic target for the prevention of VC and cardiovascular disease in patients with chronic kidney disease. Abstract : Supplemental Digital Content is available in the text.